Changing Minds: Methodological Proposal to Train Graphomotricity in Early Childhood Education - Martínez García, Mar; Martín Hernán, Guadalupe (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
The training of the graphomotor skills is one of the main learning areas in Early Childhood Education. The capacity to manipulate a series of tools to produce traces and marks is just a means that will eventually evolve into writing.  One of the most relevant skills that children will have develop in order to adapt themselves to the social and cultural context they are living in. Besides its high relevance, there is yet a lack of questioning on the adequacy of the methodological strategies widely employed. In this article we revise the concept of graphomotor skills as opposed to pre-writing skills, analysing the educational implications of using one or another methodological approach. Likewise we will make a series of proposals at both methodological and resource level, to promote the graphomotor skills in Early Childhood Education.
Keywords: graphomotricy; graphomotor competence; graphomotor skills training; psycholinguistic development; Early Childhood Education